DESENVOLVIMENTO DE UMA PLATAFORMA FOTOELETROQUÍMICA BASEADA EM SELENETO DE CÁDMIO PARA DETERMINAÇÃO DE TERC-BUTIL-HIDROQUINONA (TBHQ) - REIS, José Lucas Costa (2022)
Tert-butyl-hydroquinone (TBHQ) is a synthetic antioxidant phenolic compound applied by the food and fuel industries to avoid oxidative stress and ensure the quality and shelf life of these products. However, the excessive use of this compound can lead to potential and toxic damages to human health. In view of this, a photoelectrochemical plataform was developed through the synthesis of n-CdSe semiconductor film for the detection of TBHQ. The CdSe/FTO electrode was constructed by electrodeposition of the material on the electrode surface by cyclic voltammetry technique in a conventional three-electrode electrochemical cell. The electrochemical characterization of the material was performed by electrochemical impedance spectroscopy, analyzing the electronic properties using Mott-Schottky graphs and electrical resistance using Nyquist graphs. The optical characteristics were studied by ultraviolet-visible absorption spectrophotometry. The CdSe band gap obtained was 1.74 eV. Under the experimental and operational conditions applied to the photoelectrochemical sensor, an anodic photocurrent was obtained under an applied potential of 0.3 V in 0.1 M PBS medium at pH 7.0. The proposed sensor presented a linear response of 10 μmol L-1 to 500 μmol L-1 of TBHQ whose regression coefficient was equal to R2 = 0.9963. The modified electrode was applied to the real sample of apple juice fortified with TBHQ solution and recovery values between 89.60% to 98.80% were obtained. Therefore, CdSe/FTO is a promising photoelectrochemical platform for TBHQ determination.